Within‐ and Between‐Family Associations of Marital Functioning and Child Well‐being. Issue 2 (28th September 2016) - Knopp, Kayla; Rhoades, Galena K.; Allen, Elizabeth S.; Parsons, Aleja; Ritchie, Lane L.; Markman, Howard J.; Stanley, Scott M.
Abstract: This study clarifies within‐family and between‐family links between marital functioning and child well‐being. Expanding on existing prospective research, this study tests whether changes in parents' marital functioning are associated with corresponding changes in their children's well‐being, independent from associations that exist when comparing different families. Participants ( N = 1, 033) were members of married, opposite‐sex couples with children who participated in five waves of a larger study of marriage in the U.S. Army. Spouses' constructive communication, verbal conflict, and marital satisfaction each showed between‐family associations with parent‐reported child internalizing and externalizing problems. In contrast, within‐family associations were significant only for parents' communication behaviors. That is, parents who reported lower levels of marital satisfaction also reported lower child well‐being, whereas change in parents' communication was associated with change in child well‐being over time. Isolating within‐family effects is important for understanding marital and child functioning and for identifying potential targets for effective intervention.